Psihološke značilnosti bolnikov po amputaciji prstov ob prvi ambulantni obravnavi na Univerzitetnem rehabilitacijskem inštitutu Republike Slovenije - Soča - Horvat Rauter, Barbara (Rehabilitacija (Ljubljana), 2015)
Background: Amputation is defined as the loss or removal of a limb or its part. This loss is not just physical - it also impacts the individual%s psychological and social life. The majority of patients after finger amputation have their first examination at the outpatient clinic for orthotics and prosthetics during the first six months after amputation. Their first meeting with a psychologist therefore also happens in this time-period. The aim of our study was to survey the psychological status of the patients after finger amputation upon their first psychological examination. Methods: 34 patients after finger amputation who had their first psychological examination between September 2013 and June 2015, were included in the survey. We analysed their patient histories. Inclusion and exclusion criterions were taken into consideration. The first psychological assessment was a semi-structured interview. We designed it based on the findings of the Desmond and MacLachlan%s review. All participants were treated at the Outpatient Clinic for Orthotics and Prosthetics and were referred to the psychologists. The conversation with each participant lasted approximately one hour. Results: The results show statistically significantly lower evaluation of self-experience after finger amputation in comparison to the evaluation before the loss. The correlation between the number of amputated fingers and the evaluation of self-experience was not statistically significant. The majority of the participants wanted prosthetic care in order to fix their appearance rather than to improve the function of their hands. Conclusions: Patients after finger amputation are at various stages of mourning during their first visit to the prosthetics and orthotics outpatient clinic. This is why the psychologist must be flexible in order to identify the phase and get attuned to the patient. The results support the theory of acceptance process after experiencing amputation. People after limb loss accept the reduced ability of the limb more efficiently in comparison to the changes of their appearance.
Keywords: acceptance; amputacija; Amputation; doživljanje sebe; Fingers; Grief; mourning; prsti; self-experience; sprejemanje; žalost; žalovanje